2014
DOI: 10.4081/ija.2014.583
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic traits and deoxynivalenol contamination of two tetraploid wheat species (Triticum turgidum spp. durum, Triticum turgidum spp. turanicum) grown strictly under low input conditions

Abstract: An evaluation of the agronomic performance of two tetraploid wheat varieties (Triticum turgidum spp. durum, Claudio; Triticum turgidum spp. turanicum, Kamut ® ) grown strictly under low input conditions was carried out over three consecutive cropping years. The study reported grain yield values ranging from 1.8 to 2.6 t ha -1 . Productivity showed to be primarily affected by environmental conditions, while no differences were observed between the two genotypes. The study of the yield components highlighted tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…A significant effect of variety was observed for test weight. These results are in line with those of Dinelli et al [35], who found no significant year effect on this trait in durum wheats grown in northern Italy in low-input management. However, the Y × G interaction suggested that growing season had also a significant influence on the test weight, with the second year favoring higher values.…”
Section: Quality Traitssupporting
confidence: 93%
“…A significant effect of variety was observed for test weight. These results are in line with those of Dinelli et al [35], who found no significant year effect on this trait in durum wheats grown in northern Italy in low-input management. However, the Y × G interaction suggested that growing season had also a significant influence on the test weight, with the second year favoring higher values.…”
Section: Quality Traitssupporting
confidence: 93%
“…The severity of foliar diseases showed a slightly significant effect of rotational position. It averaged 6.66 ± 0.2% in the first cereal, and was 98.7% higher in the second cereal position, which was possibly an effect of accumulated inoculum after a previous cereal, although oats should not be a host of wheat parasites [35]. Differences between species followed the trends observed in the previous years, with emmer being by far the most affected by foliar diseases, with an average of 27.7 ± 0.05%.…”
Section: Foliar Diseases Severitymentioning
confidence: 71%
“…Previous studies from our research group suggested the suitable use of old non‐dwarf wheat varieties (both common and durum wheat) in low‐input agricultural systems . In fact, even if they have several agronomic drawbacks such as lodging problems and generally lower productivity, it was shown that, on the whole, modern and old varieties have similar yield under low‐input management.…”
Section: Introductionmentioning
confidence: 94%